Extraction of gaharu essential oil using spinning band distillation - Ahmad Fadzli, Zakaria (2006)
Gaharu is known as one of the most expensive wood in the world. Its essential oil is used in many industries such as perfume and also toiletries. The gaharu that was used in this study is grade C gaharu from peninsular of Malysia (Aquiliria Malaccensis) or known as ‘karas’ among the locals. Traditionally, gaharu oil is extracted by distilling the grinded gaharu sample in a copper still. However the process it is not effective and the yield of oil is relatively small and it acquire high temperature. The extraction of gaharu essential oil using spinning band distillation (batch distillation) and water as solvent at heating rate and temperature cut ranging from 20 – 40% and 25 - 100°C respectively was studied. The size of gaharu particle that will be used is <1.00mm. Result obtained after the experiment is 0% of oil yield in parameter stated. This extraction technique is not suitable to extract the gaharu essential oil at specified parameter. Some changes need to be done to make such objective achievable.